The highly accurate anteriolateral portal for injecting the knee - Chavez-Chiang Colbert E; Sibbitt Wilmer L; Band Philip A; Chavez-Chiang Natalia R; DeLea Suzanne L; Bankhurst Arthur D (BMC, 2011)
Abstract Background The extended knee lateral midpatellar portal for intraarticular injection of the knee is accurate but is not practical for all patients. We hypothesized that a modified anteriolateral portal where the synovial membrane of the medial femoral condyle is the target would be highly accurate and effective for intraarticular injection of the knee. Methods 83 subjects with non-effusive osteoarthritis of the knee were randomized to intraarticular injection using the modified anteriolateral bent knee versus the standard lateral midpatellar portal. After hydrodissection of the synovial membrane with lidocaine using a mechanical syringe (reciprocating procedure device), 80 mg of triamcinolone acetonide were injected into the knee with a 2.0-in (5.1-cm) 21-gauge needle. Baseline pain, procedural pain, and pain at outcome (2 weeks and 6 months) were determined with the 10 cm Visual Analogue Pain Score (VAS). The accuracy of needle placement was determined by sonographic imaging. Results The lateral midpatellar and anteriolateral portals resulted in equivalent clinical outcomes including procedural pain (VAS midpatellar: 4.6 ± 3.1 cm; anteriolateral: 4.8 ± 3.2 cm; p = 0.77), pain at outcome (VAS midpatellar: 2.6 ± 2.8 cm; anteriolateral: 1.7 ± 2.3 cm; p = 0.11), responders (midpatellar: 45%; anteriolateral: 56%; p = 0.33), duration of therapeutic effect (midpatellar: 3.9 ± 2.4 months; anteriolateral: 4.1 ± 2.2 months; p = 0.69), and time to next procedure (midpatellar: 7.3 ± 3.3 months; anteriolateral: 7.7 ± 3.7 months; p = 0.71). The anteriolateral portal was 97% accurate by real-time ultrasound imaging. Conclusion The modified anteriolateral bent knee portal is an effective, accurate, and equivalent alternative to the standard lateral midpatellar portal for intraarticular injection of the knee. Trial Registration ClinicalTrials.gov: NCT00651625